Investigating the factors influencing blended learning success for System Analysis and Design Course in Universiti Utara Malaysia - Duhaim, Saif Muttair (2016)
System Analysis and Design (SAD) is one of the core courses offered in Bachelor’s degree programme in Computer Science because its lessons are requisites in becoming system analyst, computer programmer and project leader. However, it is observed that students are not grasping the details of the lessons, and this is affecting their employability and the productivity value in the software development chain. This experience is linked to the presently-used teaching method. In this regard, blended learning model, which improves students’ learning experience and reduces underachievement in computer science, is suggested. Specifically, the generality of the factors that must be considered to achieve students’ academic success in SAD has not been adequately and empirically investigated. This study therefore aims (1) to identify factors that effect the success of blended learning model for the teaching and learning of SAD, (2) to identify the relationship between the success factors and academic success of SAD, and (3) to identify the effects of the success factors on academic success of SAD. To achieve these objectives, a quantitative research method was employed, involving administration of survey instruments distributed to 151 students using simple random sampling, and data collected were analysed using correlation and regression. The study found that students’ attitude, students’ technology usage level, students’ access to technology, students’ courseware, curriculum, learning system interface quality, lecture quality, and e-learning system comprehensiveness positively influence students’ academic success in SAD.